Analisa Hukum Peran BAPPEBTI terhadap Affiliator dan Pengguna Binary Option Berkedok Investasi dan Trading - Rila Kusumaningsih (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
Binary Options are something new in the investment world in Indonesia. It can be seen that in the digital era, various kinds of investments have emerged, such as stocks, bonds, gold, and others. The emergence of Binary Options as a form of investment led to various responses from the public, both from users and observers. The method used is in the form of a juridical-normative approach, based on its descriptive-analytical nature, the source of the data obtained is through the library research method (library study) Binary options which are always associated with futures contracts because there are several aspects that are considered to have similarities, including commodity prices. namely in the form of currency (forex) and crypto. Also, the similar appearance as in futures contracts and the need for deposits made by binary options users in the form of US Dollars and Rupiahs causes the binary option position to enter the realm of authority from Bappebti. provide legal solutions both preventive and repressive. The role of Bappebti in this case is to implement and strengthen the supervisory system in order to control and eliminate Binary Option so that it is no longer used by the public and conduct legal socialization by working with various stakeholders to inform the public of the negative impact of using Binary Option, because it is actually an illegal activity, self-defeating and causing legal consequences.